What have we learned about Australia’s swampy meadows? a literature review - Alex Sun; Floris F. van Ogtrop (Wetlands Ecology and Management, 2026)
Scientists coined the term ‘swampy meadows’ over thirty years ago to describe a type of low-energy, discontinuous watercourse found in the valley fills of Southeastern Australia. Swampy meadows are believed to provide important ecosystem services, such as wildlife conservation and water security; but to assess these claims, scientists must first understand the hydrology, geomorphic history, cultural value, and ecological significance of swampy meadows. In this paper, we reviewed literature from The Web of Science, Scopus, and Google Scholar to find that most published articles on swampy meadows are geomorphological studies of degraded systems. While these studies are important and must continue, we argue that they alone are insufficient to resolve the longstanding debates surrounding swampy meadow conservation and restoration. To make further progress on these debates, scientists should compare swampy meadows across multiple catchments, especially those that are still considered ‘intact’, and expand the scope of their current research to include topics such as biology and socio-economy. Scientists should also address directly the questions and claims raised in grey literature on the costs and benefits of restoring swampy meadows. We argue that the most effective way to protect swampy meadows is to first identify the cultural values and ecosystem services they provide, then establish management policies around these values and services.

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Hums in the humus: opportunities and challenges for soil ecoacoustics - Alex F. Taylor; Martin F. Breed; Carlos Abrahams; Amy Annells; Tom Bradfer-Lawrence; Timothy Cavagnaro; Carolyn-Monika Görres; Martin M. Gossner; Craig Liddicoat; Simon Linke; Oliver C. Metcalf; Louise Roberts; et al. (Trends in Ecology & Evolution, 2026)

Polyoxometalate-based MOF derived Co2N/Co3W3C/coal-based carbon fibers self-supporting catalyst for efficient hydrogen evolution - Shengjiao Wen; Ruiying Wang; Xingchao Wang; Mengran Lou; Yang Wang; Yuhu Feng; Alex Trukhanov; Zhipeng Sun; Xia Kong (Fuel, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

VOCs-driven ozone extremes during dry and wet heatwaves in the Jiangsu–Shandong–Henan–Anhui Boundary: Integrating meteorological forcings and SHAP interpretation - Chaolong Wang; Sufan Zhang; Yisheng Zhang; Shanshan Cui; Xiaofei Qin; Alex Guenther; Jianhui Bai; Dasa Gu; Jinhua Du; Jingchao Tang; Wanxiang Yao; Ming Wang; et al. (Atmospheric Research, 2026)

One for all and all for one health: Harmonizing SARS-CoV-2 wastewater surveillance results across a laboratory network - Alex H.S. Chik; Christopher Adam; Jane J.Y. Ho; Taylor Aris; Eric J. Arts; R. Stephen Brown; David Bulir; Ryland Corchis-Scott; Christopher T. DeGroot; Robert Delatolla; Philip Dennis; Hadi A. Dhiyebi; et al. (Science of The Total Environment, 2025)

Artificial intelligence for prediction of shelf-life of various food products: Recent advances and ongoing challenges - Mahdi Rashvand; Yuqiao Ren; Da-Wen Sun; Julia Senge; Christian Krupitzer; Tobi Fadiji; Marta Sanzo Miró; Alex Shenfield; Nicholas J. Watson; Hongwei Zhang (Trends in Food Science & Technology, 2025)

Identification and experimental validation of PYCARD as a crucial PANoptosis-related gene for immune response and inflammation in COPD - Rui Shi; Renwen Liang; Fang Wang; Lueli Wang; Wuyi Zidai; Jie Zhang; Luo Min; Xiaohua Du; Shibo Sun; Chuang Xiao; Chaozhong Li; Xuewu Liang; et al. (Apoptosis, 2024)

Photoreceptors inhibit pathological retinal angiogenesis through transcriptional regulation of Adam17 via c-Fos - Xudong Wang; Tianxi Wang; Satoshi Kaneko; Emil Kriukov; Enton Lam; Manon Szczepan; Jasmine Chen; Austin Gregg; Xingyan Wang; Angeles Fernandez-Gonzalez; S. Alex Mitsialis; Stella Kourembanas; et al. (Angiogenesis, 2024)
Pathological retinal angiogenesis profoundly impacts visual function in vascular eye diseases, such as retinopathy of prematurity (ROP) in preterm infants and age-related macular degeneration in the elderly. While the involvement of photoreceptors in these diseases is recognized, the underlying mechanisms remain unclear. This study delved into the pivotal role of photoreceptors in regulating abnormal retinal blood vessel growth using an oxygen-induced retinopathy (OIR) mouse model through the c-Fos/A disintegrin and metalloprotease 17 (Adam17) axis. Our findings revealed a significant induction of c-Fos expression in rod photoreceptors, and c-Fos depletion in these cells inhibited pathological neovascularization and reduced blood vessel leakage in the OIR mouse model. Mechanistically, c-Fos directly regulated the transcription of Adam17 a shedding protease responsible for the production of bioactive molecules involved in inflammation, angiogenesis, and cell adhesion and migration. Furthermore, we demonstrated the therapeutic potential by using an adeno-associated virus carrying a rod photoreceptor-specific short hairpin RNA against c-fos which effectively mitigated abnormal retinal blood vessel overgrowth, restored retinal thickness, and improved electroretinographic (ERG) responses. In conclusion, this study highlights the significance of photoreceptor c-Fos in ROP pathology, offering a novel perspective for the treatment of this disease.

Image-based volume estimation for food in a bowl - Wenyan Jia; Boyang Li; Qi Xu; Guangzong Chen; Zhi-Hong Mao; Megan A. McCrory; Tom Baranowski; Lora E. Burke; Benny Lo; Alex K. Anderson; Gary Frost; Edward Sazonov; et al. (Journal of Food Engineering, 2024)

Parenting Practices Are Associated With Adolescent Food Choices During Independent Eating Occasions - Marla Reicks; Karina R. Lora; Yichen Jin; Alex K. Anderson; Lillie Monroe-Lord; Blake L. Jones; Glade L. Topham; Jinan Banna; Carolyn Gunther; Laura C. Hopkins; Rickelle Richards; Siew Sun Wong (Journal of the Academy of Nutrition and Dietetics, 2023)

Adolescent Independent Eating Occasions, Dietary Intake, and Parenting Practices During the COVID-19 Pandemic: A Qualitative Study of Parents and Adolescents From Households With Low Income - Carolyn Gunther; Jinan Banna; Blake L. Jones; Catherine Park; Marla Reicks; Rickelle Richards; Heather Schier; Glade L. Topham; Siew Sun Wong; Alex K. Anderson; Miriam Ballejos; Laura C. Hopkins; et al. (Journal of Nutrition Education and Behavior, 2023)

Retinal microvasculature is a potential biomarker for acute mountain sickness - Yuan Xie; Diya Yang; Alex S. Huang; Yiquan Yang; Ying Han; Yunxiao Sun; Kai Cao; Huaizhou Wang; Shizheng Wu; Qiang Zhu; Guozhong Wang; Tianyi Wu; et al. (Science China Life Sciences, 2023)

Middle Miocene paleoenvironmental change and paleoelevation of the Lunpola Basin, Central Tibet - Jimin Sun; Jianguo Li; Weiguo Liu; Brian F. Windley; Alex Farnsworth; Chunsheng Jin; Zhiliang Zhang; Wenjiao Xiao (Global and Planetary Change, 2023)

Prenatal exposure to polycyclic aromatic hydrocarbons is not associated with behavior problems in preschool and early school-aged children: A prospective multi-cohort study - Erin R. Wallace; Erin Buth; Adam A. Szpiro; Yu Ni; Christine T. Loftus; Erin Masterson; Drew B. Day; Bob Z. Sun; Alexis Sullivan; Emily Barrett; Ruby HN. Nguyen; Morgan Robinson; et al. (Environmental Research, 2023)

Nephrotoxicity Profile of Cadmium Revealed by Proteomics in Mouse Kidney - Xi Sun; Yanwei Wang; Tingya Jiang; Xiao Yuan; Zhen Ren; Alex Tuffour; Haitao Liu; Yang Zhou; Jie Gu; Haifeng Shi (Biological Trace Element Research, 2021)

Mechanistic Deconvolution of Oral Absorption Model with Dynamic Gastrointestinal Fluid to Predict Regional Rate and Extent of GI Drug Dissolution - Alex Yu; Mark J. Koenigsknecht; Bart Hens; Jason R. Baker; Bo Wen; Trachette L. Jackson; Manjunath P. Pai; William Hasler; Gordon L. Amidon; Duxin Sun (The AAPS Journal, 2020)

Mechanistic Fluid Transport Model to Estimate Gastrointestinal Fluid Volume and Its Dynamic Change Over Time - Alex Yu; Trachette Jackson; Yasuhiro Tsume; Mark Koenigsknecht; Jeffrey Wysocki; Luca Marciani; Gordon L. Amidon; Ann Frances; Jason R. Baker; William Hasler; Bo Wen; Amit Pai; et al. (The AAPS Journal, 2017)

Stability and Reproducibility Underscore Utility of RT-QuIC for Diagnosis of Creutzfeldt-Jakob Disease - Maria Cramm; Matthias Schmitz; André Karch; Eva Mitrova; Franziska Kuhn; Bjoern Schroeder; Alex Raeber; Daniela Varges; Yong-Sun Kim; Katsuya Satoh; Steven Collins; Inga Zerr (Molecular Neurobiology, 2016)
Real-time quaking-induced conversion (RT-QuIC) allows the amplification of miniscule amounts of scrapie prion protein (PrP Sc ). Recent studies applied the RT-QuIC methodology to cerebrospinal fluid (CSF) for diagnosing human prion diseases. However, to date, there has not been a formal multi-centre assessment of the reproducibility, validity and stability of RT-QuIC in this context, an indispensable step for establishment as a diagnostic test in clinical practice. In the present study, we analysed CSF from 110 prion disease patients and 400 control patients using the RT-QuIC method under various conditions. In addition, “blinded” ring trials between different participating sites were performed to estimate reproducibility. Using the previously established cut-off of 10,000 relative fluorescence units (rfu), we obtained a sensitivity of 85 % and a specificity of 99 %. The multi-centre inter-laboratory reproducibility of RT-QuIC revealed a Fleiss’ kappa value of 0.83 (95 % CI: 0.40–1.00) indicating an almost perfect agreement. Moreover, we investigated the impact of short-term CSF storage at different temperatures, long-term storage, repeated freezing and thawing cycles and the contamination of CSF with blood on the RT-QuIC seeding response. Our data indicated that the PrP Sc seed in CSF is stable to any type of storage condition but sensitive to contaminations with blood (>1250 erythrocytes/μL), which results in a false negative RT-QuIC response. Fresh blood-contaminated samples (3 days) can be rescued by removal of erythrocytes. The present study underlines the reproducibility and high stability of RT-QuIC across various CSF storage conditions with a remarkable sensitivity and specificity, suggesting RT-QuIC as an innovative and robust diagnostic method.

Evidence for and characterization of nervous necrosis virus infection in Pacific cod (Gadus macrocephalus) - Ming-Guang Mao; Shi-Hui Wen; Alex Perálvarez-Marín; Hua Li; Jie-Lan Jiang; Zhi-Qiang Jiang; Xing Li; Hang Sun; Hui-Qian Lü (Archives of Virology, 2015)

A regional modeling study of the diurnal cycle in the lower troposphere in the south-eastern tropical Pacific - Thomas Toniazzo; Fengpeng Sun; Carlos R. Mechoso; Alex Hall (Climate Dynamics, 2013)

An integrated framework for software to provide yield data cleaning and estimation of an opportunity index for site-specific crop management - Wei Sun; Brett Whelan; Alex B. McBratney; Budiman Minasny (Precision Agriculture, 2013)

Consulting Forestry / Certification and Ecosystem Services - James Coufal; Carl Wiedemann; Jacob Gorman; Larry Teeter; Yaoqi Zhang; Michael Kilgore; Kristell Miller; Stephanie Snyder; Sun Chang; Miriam Davis; Stanley Asah; J. Mark Fly; et al. (Journal of Forestry, 2011)
45The industrialization of the United States throughout the 19th century resulted in the exploitation of millions of acres of timberland across the country. Logging during that era was described by critics as “cut out and get out” because the land was usually abandoned after the merchantable timber was exhausted. Concern about future timber supplies and the effect of logging on watersheds spurred the development of professional forestry after the Civil War. The first forestry leaders, including Bernhard Fernow and Gifford Pinchot, encouraged private non-industrial forest owners to sustainably manage their woodlands and specifically warned against destructive logging practices—including “cutting the best and leaving the rest”—aka high-grading. During the 1920s and 30s both the Forest Service and SAF spurred initiatives to encourage sustainable timber harvesting practices on private forestland. Although great progress has been made in forest management, logging on most private non-industrial forest land in the east has not changed significantly since the 19th century. Landowners usually sell timber without using the services of a forester, allowing the buyer to selectively cut the most valuable trees in the woodlot. Although this can reduce future value by 70-90%, it remains common practice because both the landowner and the timber buyer maximize short term income. The timber value and productivity of millions of acres of woodland throughout the United States have been significantly degraded as a result. This paper will trace the history of high-grading as described by forestry leaders from the 19th century through the 21st and will show that much work remains unfinished.

A New In Situ Brain Perfusion Flow Correction Method for Lipophilic Drugs Based on the pH-Dependent Crone-Renkin Equation - Alex Avdeef; Na Sun (Pharmaceutical Research, 2011)

Physicochemical Selectivity of the BBB Microenvironment Governing Passive Diffusion—Matching with a Porcine Brain Lipid Extract Artificial Membrane Permeability Model - Oksana Tsinman; Konstantin Tsinman; Na Sun; Alex Avdeef (Pharmaceutical Research, 2011)

In situ identification of polyphosphate‐ and polyhydroxyalkanoate‐accumulating traits for microbial populations in a biological phosphorus removal process - Wen‐Tso Liu; Alex T. Nielsen; Jer‐Horng Wu; Chin‐Sun Tsai; Yoshitaka Matsuo; Søren Molin (Environmental Microbiology, 2001)
Polyphosphate‐ and polyhydroxyalkanoate (PHA)‐accumulating traits of predominant microorganisms in an efficient enhanced biological phosphorus removal (EBPR) process were investigated systematically using a suite of non‐culture‐dependent methods. Results of 16S rDNA clone library and fluorescence in situ hybridization (FISH) with rRNA‐targeted, group‐specific oligonucleotide probes indicated that the microbial community consisted mostly of the α‐ (9.5% of total cells), β‐ (41.3%) and γ‐ (6.8%) subclasses of the class Proteobacteria , Flexibacter–Cytophaga (4.5%) and the Gram‐positive high G+C (HGC) group (17.9%). With individual phylogenetic groups or subgroups, members of Candidatus Accumulibacter phosphatis in the β‐2 subclass, a novel HGC group closely related to Tetrasphaera spp., and a novel γ‐proteobacterial group were the predominant populations. Furthermore, electron microscopy with energy‐dispersive X‐ray analysis was used to validate the staining specificity of 4,6‐diamino‐2‐phenylindole (DAPI) for intracellular polyphosphate and revealed the composition of polyphosphate granules accumulated in predominant bacteria as mostly P, Ca and Na. As a result, DAPI and PHA staining procedures could be combined with FISH to identify directly the polyphosphate‐ and PHA‐accumulating traits of different phylogenetic groups. Members of Accumulibacter phosphatis and the novel gamma‐proteobacterial group were observed to accumulate both polyphosphate and PHA. In addition, one novel rod‐shaped group, closely related to coccus‐shaped Tetrasphaera , and one filamentous group resembling Candidatus Nostocoidia limicola in the HGC group were found to accumulate polyphosphate but not PHA. No cellular inclusions were detected in most members of the α‐ Proteobacteria and the Cytophaga–Flavobacterium group. The diversified functional traits observed suggested that different substrate metabolisms were used by predominant phylogenetic groups in EBPR processes.

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)